Examining the Relationship between Caregiver Mentalized Affectivity and Childhood Defense Mechanisms. (2nd October 2021) - Dunn, Hannah; Rudenstine, Sasha; Tuber, Steve; Jurist, Elliot
ABSTRACT: Mentalized affectivity is the ability to draw from prior and present contexts to evaluate and modulate one's emotions. Defense mechanisms are unconscious psychological strategies used to protect a person from anxiety arising from unacceptable thoughts or feelings. The present study explores the relationship between caregivers' mentalized affectivity and children's defense mechanisms. Children who underwent a neuropsychological assessment or an individual psychotherapy intake at a low-fee outpatient mental health clinic were recruited (N = 24 dyads). Caregivers completed the Brief Mentalized Affectivity Scale (BMAS), a 12-item self-report questionnaire to assess three components of mentalized affectivity: identifying, processing, and expressing of emotions. Children completed the Thematic Apperception Test (TAT); responses were coded based on Cramer's Defense Mechanism Manual. The findings of the analysis are consistent with the hypothesis that denial is more prevalent at younger ages (<8 years), while identification is more common in latency and adolescence (>8 years). Among children older than 8 years old, lower caregiver mentalized affectivity was associated with significantly more primitive defense use (i.e., denial) on the part of the child. Although there were limitations to the findings, results from this exploratory study have important implications for caregiver-child therapeutic interventions and warrant further examination as the sample size grows.